2020
DOI: 10.1302/2633-1462.19.bjo-2020-0116.r1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and hip fractures: impact and lessons learned

Abstract: Aims The coronavirus disease (COVID)-19 pandemic forced an unprecedented period of challenge to the NHS in the UK where hip fractures in the elderly population are a major public health concern. There are approximately 76,000 hip fractures in the UK each year which make up a substantial proportion of the trauma workload of an average orthopaedic unit. This study aims to assess the impact of the COVID-19 pandemic on hip fracture care service and the emerging lessons to withstand any future outbreaks. Methods Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 7 publications
4
81
0
3
Order By: Relevance
“…Arafa et al demonstrated a significant increase in the amount of PFFs during the pandemic period (61.7%). In contrast, Maniscalco et al examined the period of February to March 2019 in comparison to the corresponding months of 2020 and demonstrated a decrease of 28.4% (169 vs. 121) in PFF incidence; similar results were demonstrated by Slullitel et al [ 31 , 32 , 34 ] Compared to these studies, our present study encompassed the entire year of 2020 and included a larger patient cohort. Furthermore, our study included a sub-analysis based on the presence of lockdown measures.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Arafa et al demonstrated a significant increase in the amount of PFFs during the pandemic period (61.7%). In contrast, Maniscalco et al examined the period of February to March 2019 in comparison to the corresponding months of 2020 and demonstrated a decrease of 28.4% (169 vs. 121) in PFF incidence; similar results were demonstrated by Slullitel et al [ 31 , 32 , 34 ] Compared to these studies, our present study encompassed the entire year of 2020 and included a larger patient cohort. Furthermore, our study included a sub-analysis based on the presence of lockdown measures.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have demonstrated conflicting findings regarding the effect of Covid-19 on the incidence of PFFs [ 31 35 ]. Arafa et al demonstrated a significant increase in the amount of PFFs during the pandemic period (61.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Our search returned 253 articles on PubMed published from December 2019 to December 2020, one article on Cochrane published in October 2018, and 308 articles on EMBASE all published in 2020. After discarding duplicates, screening for inclusion criteria, and applying exclusion criteria, 19 articles were selected for qualitative analysis [7][8][9][10][11][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and 17 for quantitative analysis (Fig. 1) [7-11, 19-29, 31].…”
Section: Search Resultsmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19), caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is an international public health emergency. As of December 11, 2020, over 69.6 million cases and approximately 1.58 million deaths have been reported worldwide [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have found that a patient sustaining a hip fracture with concomitant COVID-19 infection has a significantly increased mortality rate. Wright et al found a mortality rate of 11.7% (2/17) [ 5 ], Vives et al 30.4% (7/23) [ 6 ], Kayani et al 30.5% (25/82) [ 7 ], Hall et al 33.3% (9/27) [ 8 ], Egol et al 35.3% (6/17) [ 9 ], Arafa et al 36.8% (7/19) [ 10 ], Wignall et al 38.2% (13/24) [ 11 ] and Farii et al 40% (20/50) [ 12 ]. Similarly, meta-analyses conducted by Wang et al (16 studies) and Lim and Pranata (6 studies) found mortality rates of 32.6% [ 13 ] and 36% [ 14 ], respectively.…”
Section: Introductionmentioning
confidence: 99%